Poly (Amic) Acid Improves the Efficiency and Stability of PtCr Nanoparticle Catalyst during Ethanol Oxidation Reaction. Issue 12 (1st January 2017) - Zhang, Jing; Yazgan, Idris; Kariuki, Victor M.; Sadik, Omowunmi A.
Abstract : Platinum based nanoparticles have attracted increasing attention as candidates for high performance electrocatalysts for applications in ethanol fuel cells. However, the primary challenge has been attributed to the loss of the catalyst into solution. We hereby demonstrate an approach using poly (amic) acid (PAA) films as supporting material in order to improve the stability and inherently the efficiency of the catalysts. Alloyed PtCr nanoparticles were fabricated via electrodeposition on a glassy carbon electrode to improve the efficiency of ethanol oxidation reaction (EOR) in acidic media. Cyclic voltammetry was used for the deposition and the potential was scanned from −1.5 V to 0.5 V at the scan rate of 10 mV s −1 for 40 cycles. The general size of the PtCr nanoparticles were determined to be ∼105 nm and the surface aggregates were from 400 nm to 1 μm at 40 cycles. This catalyst was created via spin coating of PAA layer (thickness ∼4 μM) on the surface of PtCr alloy. The catalyst/PAA combination permitted the diffusion of ethanol toward the surface of the PtCr nanoparticles resulting in efficient reduction while simultaneously preventing the loss of the catalyst into the solution. Electrode stability of 900 cycles (three days) was recorded at varying potential scan cycles. This electrode coated with PAA was found to be three times as durable when compared with the bare catalysts surface. This work could allow the widespread use of alloyed PtCr nanoparticles/PAA combination for stable and efficient electrochemical reduction of ethanol.